The Combination of Dosages of NPK Fertilizer and Concentration of Rabbit Liquid Organic Fertilizer on Yield And Quality of Cauliflower Plants (Brassica oleracea var. Botrytis L) - Nora Augustien (INFOKUM, 2024)
Cauliflower (Brassica oleracea var. Botrytis L.) is a seasonal crop with high economic value and health benefits. The increasing demand for cauliflower that is greater than the rate of food production will increase the potential for a food crisis. This study aims to determine the combination of NPK fertilizer application with Rabbit Liquid Organic Fertilizer on the yield and quality of cauliflower. This study used a 2 Factorial Randomized Group Design of 4 levels each repeated 3 times so that there were 48 experimental units with each unit containing 3 polybags of sample plants. The first factor is the dose of NPK fertilizer consisting of 4 levels, namely 0 gr/plant (M0), 5 gr/plant (M1), 6.25 gr/plant (M2), and 7.5 gr/plant (M3). The second factor is the concentration of Rabbit POC 0 ml/L (K0), 30 ml/L (K1), 45 ml/L (K2), 60 ml/L (K3). The results of the study are: 1) There is a real interaction in the treatment of a combination of doses of NPK Fertilizer and Rabbit Liquid Organic Fertilizer on the mass weight of flowers; 2) the effect of NPK Fertilizer dose treatment of 7.5 grams/plant (M3) singly has a real effect on the parameters of plant crown diameter (77.06 cm) and a very real effect on the circumference of the flower mass (33.67 cm); 3) The dose treatment of 60 ml/L Rabbit Liquid Organic Fertilizer (K3) significantly influenced the parameters of per-plant crown diameter (78.19 cm) and had a very significant effect on the circumference of flower mass (33.54 cm).